The Implementation of the Family Hope Program in Alleviating Poverty in Lamurukung Village Tellusiatinge District Bone Regency - Mardi Mardi; Abdul Rahman (Jurnal Ad'ministrare, 2022)
Poverty is one of the biggest problems faced by the Indonesian people today. One of the steps taken by the government to deal with poverty is to implement the Family Hope Program is right on target for the poor. This study aims to determine the application of the Family Hope Program in alleviating poverty in Lamurukung Village, Tesllu Siattingnge District, Bone Regency. The method of the research is descriptive with a qualitative approach. The data research was collected through structured interview techniques. And the data analysis technique uses data reduction, data presentation, and conclusion drawing. The results of this study indicate that the implementation of the Family Hope Program has been running well and effectively when viewed from the four indicators of policy implementation, namely communication, resources, bureaucratic structure, and disposition, but that does not mean there are no shortcomings in implementing this program. The drawback in implementing this program is that it does not include a component of activities regarding business skills because this program only focuses on two components namely education and health.